Development of key competencies in schoolchildren through track and field - Yednak, Valeriy; Galan, Yaroslav; Ognyisty, Andriy (Педагогічна Академія: наукові записки, 2026)
This article provides a theoretical justification for the role of athletics (running, jumping, throwing, relays and reflex exercises) in the development of pupils’ key competences. It reviews official documents (the New Ukrainian School Concept, the Law ‘On Education’, and the Ministry of Education and Science’s educational standards), as well as Ukrainian and international scientific research from the last 10–15 years. A comparative analysis of key works has been carried out, and types of research and their results have been identified. A model is proposed in which athletics exercises are combined with reflection and group work to stimulate pupils’ cognitive, emotional and social skills. Objective. To substantiate the theoretical mechanisms underlying the development of key competences in schoolchildren during physical education lessons through athletics. Methods. The study utilised theoretical analysis and a review of scientific and methodological literature, official regulatory and legal documents in the field of education and physical education, as well as a comparative analysis of approaches to the development of key competences in schoolchildren. Results. As a result of the study, the interrelationship between athletics, the pedagogical mechanisms of their influence, and the development of key competences in schoolchildren has been theoretically substantiated. A conceptual model has been developed that reflects the sequence of the development of pupils’ physical, cognitive-regulatory, psycho-emotional and social skills and their connection with the development of health-preserving, communicative, socio-civic competences, critical thinking and the ability to learn throughout life. Conclusions. Athletics, as a teaching and training component of physical education lessons, has significant potential for the development of key competences in schoolchildren, combining the development of physical qualities with the formation of self-control, critical thinking, teamwork, communication and health-promoting behaviour.